The Role of Work Ethics, Work Motivation, Job Satisfaction and Compensation on Police Performance in the Digital Era - Vita Mayastinasari (Faculty of Science and Technology University of Pramita Indonesia, 2023)
The purpose of this study was to analyze the relationship between work ethics and police performance, the relationship between work motivation and police performance, the relationship between job satisfaction and police performance, the relationship between compensation and police performance, and to analyze the relationship between compensation and police performance. This study uses a quantitative method by distributing online questionnaires through social media. Respondents in this study were senior police officers who were determined by simple random sampling method with a total of 343 police officers. Data analysis in this study used structural equation modeling (SEM) with SmartPLS 3.0 software as a data processing tool. The questionnaire was designed using a Liker scale of 1 to 5. The stages of data testing were validation test, reliability test and hypothesis testing. The results of this study indicate that the work ethics variable has a positive and significant effect on police performance, the work motivation variable has a positive and significant effect on police performance, job satisfaction has a positive and significant effect on police performance, the compensation variable has a positive and significant effect on police performance.